Cohesion and performance for female and male sport teams - Eys, M. A.; Ohlert, J.; Blair Evans, M.; Wolf, S. A.; Martin, L. J.; Van Bussel, M.; Steins, C. (The Sport Psychologist, 2015)
A previous meta-analysis examining the relationship between cohesion and performance (Carron, Colman, Wheeler, & Stevens, 2002) revealed that this relationship was significantly stronger for female teams as compared with male teams. The purpose of the current study was to explore perceptions of the cohesion-performance relationship by coaches who have led teams of both genders. Semistructured interviews were employed with Canadian and German coaches with previous experience leading both male and female sport teams. The information obtained through the interviews yielded a number of categories pertaining to potential similarities and differences within female and male sport teams including: (a) the nature of cohesion (e.g., direction of the cohesion-performance relationship), (b) antecedents of cohesion (e.g., approaches to conflict), and (c) the management of cohesion (e.g., developing social cohesion). Overall, the results offer testable propositions regarding gender differences and group involvement in a sport context as well as informing best practices such that teams can attain optimal performance.